Efektifitas Media Edukasi Berbasis Audiovisual terhadap Pengetahuan dan Sikap Keluarga Lansia Hipertensi dalam Mencegah Covid-19 - Ni Luh Putu Dian Yunita Sari; Ni Made Dwi Ayu Martini; Ketut Darmaja; Ni Luh Susanti Satryani; I Gusti Agung Kumala Dewi (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2022)
Background: One of the vulnerable population in the COVID-19 pandemic is the elderly with hypertension. The family as a support system for the elderly in dealing with illness must have good knowledge and attitudes. Purpose: This study aims to determine the effectiveness of audiovisual-based educational media "Controlling Video" on the knowledge and attitudes of elderly families with hypertension in preventing covid-19. Research method: This study used a quasi-experimental design with a control group. Purposive sampling was chosen and the number of samples obtained was 64 people. The group was given audiovisual media "Controllers Video" for four weeks via whatsapp, while the control group was given media leaflets after the entire series of interventions was completed. The results of data collection were processed by the Mann-Whitney test after obtaining data that were not normally distributed. Results: There was a significant difference in the older people family with hypertension (p value <0.001) and there was a significant difference in the attitude of the elderly family with hypertension in preventing COVID-19 between the intervention and control groups (p value = 0.006). Conclusion: The results of this study can be used as study material to provide family-based interventions in improving efforts to prevent COVID-19.